INTERFERENSI BAHASA BATAK MANDAILING DALAM TUTURAN BERBAHASA INDONESIA PADA ACARA PARPUNGUAN MASYARAKAT MANDAILING KOTA JAMBI - Afif Rofii; Rizka Rani Hasibuan (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research is aimed at describing the types of Batak Mandailing language interference towards Indonesian language in the event Parpunguan masyarakat Mandailing Kota Jambi society. This research is qualitative descriptive. The data is taken from the utterances of Indonesian language which comprises Batak Mandailing language interference. The data is collected by using listening and tapping technique, observation, and speaking. The result of data analysis shows that there are grammatical interferences in the event parpunguan in Kota Jambi, namely; there are 8 utterances in the form of morpheme, there 6 utterances in the form of words, there are 28 utterances in the form phrase, there are 9 utterances in the form of clause, and there are 3 utterances in the form of sentence from those 54 data. The result of this research is being recommended to the expert of language, Badan Pembinaan dan Pengembangan Bahasa Provinsi Jambi, and head of custom to increase a kind of socialization in using Indonesian language to society correctly; Moreover, to the society who live in Kota Jambi especially Bataknese Mandailing to pay more attention to the use of Indonesian language correctly.  Keywords:  Batak Mandailing Language Interference, Indonesian Language, Parpunguan